1998
DOI: 10.1046/j.1365-2559.1998.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Gains and losses of CD44 expression during breast carcinogenesis and tumour progression

Abstract: Qualitative and quantitative changes of CD44 expression are implicated in early stages of breast carcinogenesis. The restricted neo-expression of certain CD44 isoforms in breast neoplasias suggests that CD44 might be a potential target for future antibody-based tumour therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 34 publications
6
52
0
3
Order By: Relevance
“…This indicates alternative pathways in breast carcinogenesis, as reflected by recent cytogenetic and adhesion molecule studies from our group, as well. 41,42 We conclude that in both the normal breast and benign proliferative breast diseases, there is a heterogeneous proliferation of progenitor, glandular, and myoepithelial cells as well as their intermediary antecedents in different proportions. In contrast, intraductal neoplastic breast lesions (atypical ductal hyperplasia and ductal carcinoma in situ non-high grade), are composed of one proliferating cell type, namely malignantly transformed glandular epithelial cells.…”
Section: Discussionmentioning
confidence: 86%
“…This indicates alternative pathways in breast carcinogenesis, as reflected by recent cytogenetic and adhesion molecule studies from our group, as well. 41,42 We conclude that in both the normal breast and benign proliferative breast diseases, there is a heterogeneous proliferation of progenitor, glandular, and myoepithelial cells as well as their intermediary antecedents in different proportions. In contrast, intraductal neoplastic breast lesions (atypical ductal hyperplasia and ductal carcinoma in situ non-high grade), are composed of one proliferating cell type, namely malignantly transformed glandular epithelial cells.…”
Section: Discussionmentioning
confidence: 86%
“…HER2-negative is part of the basal phenotype. Bànkfalvi et al indicated that myoepithelial cells expressed CD44 in normal breast epithelium, and that this is implicated in the early stage of breast carcinogenesis (21). Herrera-Gayol et al observed that CD44 expression was involved in two of the three steps of the invasive cascade and could not be confidently used as a reliable prognostic indicator (22).…”
Section: Discussionmentioning
confidence: 99%
“…Sanchez et al revealed a deregulation in the CD44 expression pattern in malignant tumors, but did not identify a correlation between this deregulation and clinicopathological factors (23). Conversely, Bànkfalvi et al observed that increased levels of CD44 expression were correlated with poor prognosis and metastatic involvement of the axillary lymph nodes in breast cancer (21). Looi et al revealed that CD44 played a role in the progression of breast cancer (24).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HA is clearly involved in cellular motility by virtue of its ability to form a pericellular sheath in combination with aggregating proteoglycans such as versican and aggrecan (12). Although the sheath is anchored by HA-receptors such as CD44, which have themselves been associated with outcome in breast cancer (29), the existence of sheath relies on its aggregating proteoglycan content (30). 8 To clarify the independent roles of HA and versican, in vitro studies need to be performed to determine whether versican promotes motility and invasion of breast cancer cells in the absence of a pericellular sheath of HA.…”
Section: Discussionmentioning
confidence: 99%